Legal Protection of Workers On Bankruptcy Decisions of Employing Companies - Sumarso (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Labor groups are very very vulnerable to violations of the law such as not being given decent wages and severance pay for layoffs, to avoid arbitrary actions by employers, workers are provided with legal protection facilities in the form of regulations regarding employment. Bankruptcy conditions experienced by companies will result in delays in payment of workers' wages, therefore the law provides certainty regarding the privileges granted to workers in order to get priority in paying wages owed. The purpose of this study is to find out more about bankruptcy and its impact on workers, and the expected benefits of this research as a guide for law enforcers in the scope of civil law. The formulation of the problem in this legal research is the legal protection of workers' rights based on normative law and the position of workers in the settlement of payment of workers' rights for the bankruptcy status of the employer or entrepreneur. While this type of legal research is normative legal research that uses several approaches as a method of case analysis. Everyone has the right to work in fulfilling their daily needs as regulated in the legislation. Workers as workers need legal protection from the State as a guarantor of certainty for their rights to be obtained. Through applicable regulations, the government can supervise the private sector in managing employment and can guarantee the welfare of workers. The condition of a company declared bankrupt will have a direct impact on workers such as not paying wages according to the contract, in carrying out the settlement of unpaid wages for workers there will be a debt that must be paid off by the bankrupt debtor. The settlement of the debt must take precedence according to the regulations in the Manpower Act, and the industrial relations court is no longer the court that has the authority to decide post-bankrupt industrial relations cases.